Phylogenetic analysis of pathogenic algae reveals lineage-dependent patterns of phagocytosis - Christopher D. Shave; Mohammed J. A. Haider; Chinaemerem U. Onyishi; Megan C. McDonald; Leanne Stones; Tomasz Jagielski; Robin C. May (mBio)
ABSTRACT Prototheca is an unusual genus of algae that lack chlorophyll and are obligate heterotrophs. To date, six paraphyletic pathogenic species have been identified in the context of vertebrates, principally in cattle-associated and human-associated infections. Together with the genus Auxenochlorella and Helicosporidium, rDNA sequence analysis currently favors grouping Prototheca under a clade known as the Auxenochlorella, Helicosporidium and Prototheca (AHP) lineage. Most studies so far have focused only on Prototheca bovis and Prototheca ciferrii as cattle-associated species and on Prototheca wickerhamii as a human-associated species. However, such studies remain limited in scope as they focus on only three species of Prototheca, which is not representative of the total number of species within the AHP lineage. In this study, we employ a phylogenetics approach based on five new organelle-encoded genes to delineate higher-level relationships within the AHP lineage. We use the resultant data to then guide a live-cell imaging-based investigation of aspects of the mammalian innate immune response to 11 Prototheca species and four Auxenochlorella species. Our data reveal varying patterns of phagocytosis dynamics that are both host cell type- and algal species-dependent. Together, these findings reveal the interaction between pathogen phylogeny and host immune response, revealing ways to identify new therapeutic targets in the future.IMPORTANCEProtothecosis is a rare algal infection caused by members of the genus Prototheca, which is comprised of unusual non-photosynthetic algae. Six pathogenic species have been identified so far that can cause infection in vertebrates, primarily cattle and humans. The phylogeny of this genus remains obscure and has been revised multiple times recently. However, this phylogeny has largely been based on only three species of Prototheca. To resolve this phylogenetic conundrum, here, we employ a phylogenetics approach based on five new organelle-encoded genes. We then use these data to perform live-cell imaging of a selected range of Prototheca species co-cultured with mammalian immune cells. Visualizing these phagocytic interactions in this context helps delineate both host cell-type- and species-dependent differences in phagocytic uptake, thereby providing novel insight into lineage-based differences.